Ginsenoside Rg1 Inhibits STAT3 Expression by miR-15b-5p to Attenuate Lung Injury in Mice with Type 2 Diabetes Mellitus-Associated Pulmonary Tuberculosis. (4th October 2022) - Ma, Tingxi; Mao, Xiaohui; Meng, Xiangguo; Wang, Qinghu
Abstract : Type 2 diabetes mellitus (T2DM) has been regarded as a critical risk factor for pulmonary tuberculosis (PTB). Ginsenoside Rg1 has been identified as a potential therapeutic agent for T2DM by suppressing the inflammatory response. However, the effect of Rg1 on T2DM-associated PTB has not been reported. In this study, we aimed to explore the function of Rg1 in the regulation of T2DM-associated PTB. We established a T2DM-associated PTB mouse model and found that the fibrosis of lung tissues was inhibited by Rg1 in T2DM-associated PTB mice. The lung injury of T2DM-associated PTB mice was repressed by Rg1. Moreover, the levels of IL-6, TNF- α, and IL-1 β in the lung tissues and serum were decreased by Rg1 in T2DM-associated PTB mice. The treatment with Rg1 inhibited the levels of free fatty acid and enhanced the expression of miR-15b-5p in lung tissues of T2DM-associated PTB mice. MiR-15b-5p targeted and inhibited the STAT3 expression. The expression of STAT3 was downregulated by Rg1, while the inhibition of miR-15b-5p reversed the downregulation. The expression of miR-15b-5p was reduced, but the expression of STAT3 was upregulated in the lung tissues of T2DM-associated PTB mice. We validated that miR-15b-5p attenuated inflammation and lung injury in the T2DM-associated PTB mouse model. The overexpression of STAT3 or the suppression of miR-15b-5p restored lung fibrosis and injury inhibited by Rg1 in T2DM-associated PTB mice. Meanwhile, the Rg1-repressed levels of IL-6, TNF- α, and IL-1 β were enhanced by the overexpression of STAT3 or the suppression of miR-15b-5p. In addition, the levels of free fatty acid repressed by Rg1 were reversed by STAT3 overexpression and miR-15b-5p inhibition. Thus, we conclude that ginsenoside Rg1 inhibits the STAT3 expression by miR-15b-5p to attenuate lung injury in mice with type 2 diabetes mellitus-associated pulmonary tuberculosis.